COMPARISON OF DRAINAGE COVER COSTS IN THE RUNWAY STRIP AREA USING PRECAST CONCRETE AND CONVENTIONAL CONCRETE AT FRANS SALES LEGA AIRPORT, RUTENG - Bahari Ibnu Abbas, Rindra; Suryono, Wiwid; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This study discusses a cost and time comparison of drainage cover construction using conventional concrete and precast concrete methods at Frans Sales Lega Airport. The research was motivated by the presence of open drainage channels in the runway strip area, which do not comply with the 2023 regulations issued by the Directorate General of Civil Aviation. The drainage cover was designed with dimensions of 2300 mm x 600 mm for both conventional and precast concrete. The research method used is descriptive with a quantitative approach to cost and construction time analysis, starting with data collection such as drainage layout and local unit price standards (HSPK). The process continued with moment, shear, and deflection analysis, which was then used to calculate the loading. The next steps involved designing the slab thickness and comparing both cost and duration of execution. The analysis results show that the conventional concrete method requires a total cost of IDR 3,920,834,511.00, while the precast concrete method amounts to IDR 8,786,393,521.00. In terms of duration, precast concrete is more efficient with 42 days of work compared to 83 days for conventional concrete. Based on these findings, conventional concrete is more economical in terms of cost, while precast concrete is superior in time efficiency.